Pendampingan dan Pengembangan Produk Tenunan UMKM Dua Putri Dalam Meningkatkan Nilai Jual - Eti Muliati; Fitratul Aqidah; Odesa Ramadanti; Sakinah Sakinah; Ita Purnama (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Tenunan Dua Putri is an UMKM owned by Mr. Saleh whose address in West Rabadompu. UMKM Dua Putri sells various types of typical Bima woven fabric and already has many partners in various sub-districts and offices who collaborate with this UMKM. The assistance and development provided is form of logos, packaging and marketing so that this products can be more widely known and more easily accessible to everyone. The method that we used for this development includes observation, which is at the beginning of the activity is carried out to find out what problems need to be overcome. The planning method involves planning the design, packaging, logo and marketing media. The implementation method is to notify the UMKM regarding the logo design, packaging and marketing media that have been created. Implementation method is to notify the UMKM owners that everything that has been planned from the start has been completed.